2021
DOI: 10.1021/acsomega.1c02304
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Use of CTAB-Treated Illite as an Alternative Filler for Natural Rubber

Abstract: Fillers are indispensable for rubber composites. Carbon black as an efficient reinforcing filler is most widely used in the rubber industry. However, the utilization of nonrenewable feedstock, energy consumption, and footprint for making carbon black lead to the seeking of alternative substitutes for carbon black, which is of great significance. Here in this work, the possibility of illite, a most common mineral in sedimentary rocks, as an alternative filler for natural rubber (NR) is determined. It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…As expected CTAB, BmiCl, and DmiBr increased the ν t , which probably resulted from their positive influence on the dispersion of biofiller and curing system components in the elastomer matrix. CTAB is commonly used for improving the filler-elastomer interaction [32,64]. Furthermore, CTAB as a surfactant may be preferentially adsorbed on the surface of the filler particles.…”
Section: Cure Characteristics and Crosslink Density Of Nr Composites ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As expected CTAB, BmiCl, and DmiBr increased the ν t , which probably resulted from their positive influence on the dispersion of biofiller and curing system components in the elastomer matrix. CTAB is commonly used for improving the filler-elastomer interaction [32,64]. Furthermore, CTAB as a surfactant may be preferentially adsorbed on the surface of the filler particles.…”
Section: Cure Characteristics and Crosslink Density Of Nr Composites ...mentioning
confidence: 99%
“…The application of ionic liquids is also known to positively affect the dispersion of filler and curatives and thus the properties of vulcanizates [27][28][29]. Moreover, the crucial importance of alkylammonium salts, i.e., cetyltrimethylammonium bromide (CTAB), has been reported, which acted as a substance enhancing the dispersion of solid additives in polymer matrix and consequently the properties of final products [30][31][32]. However, in many cases these reports from the literature mainly focus on the application of common fillers, i.e., silica, carbon black, or carbon nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the low content of carbon black or silica composite fillers further promoted the dispersion of coal particles in the rubber, which effectively enhanced the mechanical reinforcing properties of coal particles and the thermal stability of rubber composites. Wang Z et al [ 26 ] investigated the possibility of illite as an alternative natural rubber (NR) filler. The experimental results demonstrated that illite treated with cetyltrimethylammonium bromide (CTAB) could enhance the crosslinking density and dispersion of illite-NR, and the mechanical properties and wear resistance of illite/NR composites could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The huge reserves endow this illite with a cheaper price, which can greatly reduce the production cost of rubber products when it is used as a filler. In a previous work [ 44 ], the possibility of illite and hexadecyl trimethyl ammonium bromide (CTAB) modified counterpart as substitute filler for natural rubber (NR) has been explored. It is found that pristine illite does not reinforce NR remarkably, which is related to the weak interfacial interaction between illite and NR.…”
Section: Introductionmentioning
confidence: 99%